Pre-purchase Agreement on the Covid-19 Vaccine and its Impact on the Right to Health - Josina Augustina Yvonne Wattimena; Mariah Agnes Matakena (SASI, 2021)
A vaccine is a core solution to decreasing the widespread damage caused by the COVID-19 pandemic. However, the race to find a vaccine requires a large budget to finance research and development carried out by pharmaceutical companies. This funding is usually accommodated by wealthy developed nations who enter per-purchase agreements with these companies that guarantee a large quantity of the approved vaccines, honored in the agreements between these countries and the pharmaceutical companies. However this agreement blocks the access to other countries, especially developing countries to purchase the same vaccines therefore unable to fulfill their citizens’ right to health as regulated in the universal declaration of human rights and other international legal sources. In analyzing this, the method of research used is a legal normative approach by studying literary materials, international legal documents, and case studies. The conclusion of this research is that pre-purchase agreements are a right of developed nations to fulfill the right of their citizens on one perspective however on the other it violates the right of the international community, especially small and developing countries to fulfill their right to health.